MK-8237: a house dust mite vaccine for treating allergic rhinitis, asthma and atopic dermatitis. (1st November 2016) - Ferrando, Matteo; Bagnasco, Diego; Passalacqua, Giovanni; Varricchi, Gilda; Canonica, Giorgio Walter
ABSTRACT: Introduction: Since its introduction in clinical practice one century ago for the treatment of respiratory allergic diseases, allergen-specific immunotherapy (AIT) has exhibited a relevant clinical efficacy that was subsequently confirmed in controlled trials. Thus, AIT has been accepted worldwide, as testified by guidelines and international documents. AIT is considered pivotal in the management of allergic rhinitis with or without conjunctivitis and with or without asthma. These conditions, in addition to hymenoptera venom allergy, currently are the accepted indications. The use of AIT in house-dust mite allergy still remains debated, especially due to the methodological problems in assessing this form of respiratory allergy. The more recent experimental data on MK-8237 sublingual tablets provided evidence that AIT, in the sublingual form, is effective in dust mite allergy. Areas covered: At present, the evidence of the efficacy of AIT in conditions other than respiratory allergy are not conclusive, but encouraging results have been obtained in food allergy and atopic dermatitis. Herein, the authors discuss the data for these indications. Expert opinion: Not all patients respond to AIT in the same way. Accordingly, AIT represents a promising path to precision medicine and hopefully will be able to reduce this burden of non-responding patients.